PENGARUH PEMBERDAYAAN, SIKAP KERJA, EFIKASI DIRI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DI KANTOR OTORITAS PELABUHAN UTAMA BELAWAN - Betty .; Julianto Sembiring; Muhammad Fadhlansyah Nasution; M. Syarizal Lubis; Tuahta Ginting (JRMB (Jurnal Riset Manajemen & Bisnis), 2021)
Problem of this study what is influence of  empowerment on performance. What is influence of    work attitude on performance. What is influence of   self efficacy  on performance. What is influence of  organization culture on  performance. What is influence  empowerment,    work attitude, self efficacy  and  organization culture on   performance. The purpose of this study to determine and analyze the effect of   empowerment on   performance. Determine and analyze the effect of   work attitude on   performance. Determine and analyze the effect of self efficacy  on   performance. Determine and analyze the effect of  organization culture on   performance. Determine and analyze the effect of   empowerment,  work attitude, self efficacy  and  organization culture on   performance.  Sample in the study is 74 employees. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate  empowerment  has a positive and significant effect on performance.  Work attitude  has a positive and significant effect on   performance. Self efficacy   has a positive and significant effect on   performance.  Organization culture  has a positive and significant effect on performance.  Empowerment,  work attitude, self efficacy  and  organization culture  has a positive and significant effect on   performance.